Análisis Jurídico, Crítico y Doctrinario de la Composición de la Asamblea Nacional y sus Efectos en la Realidad Socio Económica del Ecuador. - Guamán Paqui, Segundo Baudilio (2023)
The present thesis is entitled: "Legal, Critical, and Doctrinal Analysis of the Composition of the National Assembly and Its Effects on the Socio-Economic Reality of Ecuador." It comes from a legal problem that deserves to be transformed in order to solve and overcome the socio-legal issues identified in Article 4 of the Organic Law of the Legislative Function, which stipulates the structure of the National Assembly in accordance with Article 118 of the Constitution of the Republic of Ecuador, which determines the integration of the National Assembly. Currently, the National Assembly is composed of 137 assembly members, which is an excessive number of representatives. The problem primarily lies in the fact that lawmakers are unaware of the principles on which the legal system is based, leading to legal gaps, work incompetence, a lack of understanding of social issues, and also involving high expenditure of state resources. Instead, there should be a more dynamic projection of laws in favor of Ecuadorians to ensure the legislative and oversight activities they must fulfill. Therefore, in the context of the thesis problem, it is necessary to amend the Organic Law of the Legislative Function, stipulating a reduction in the number of provincial assembly members to 48 people. This would, in some way, ensure the effectiveness and efficiency of their functions by reducing lexical problems in decision-making. Over the years, hundreds of legislators have served, most of whom have little to no experience, legal knowledge, or expertise of any kind. They lack connections to the essential sciences required to manage the system and have not maintained stable political ideologies. They have created laws that have primarily served their interests in the socio-legal sphere. This is why it is necessary in Ecuador to provide the legal certainty that these officials should offer. In addition to all of the above, we should consider the positive aspect of reducing the number of assembly members, which would result in economic savings in the General State Budget. This savings should be allocated to healthcare, education, housing, and the well-being of the Ecuadorian people.